2019
DOI: 10.4236/fns.2019.105039
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns and Their Association with Depression among Type 2 Diabetes Patients in Gaza Strip, Palestine

Abstract: Background: Depression is a common mental disorder. Globally, more than 340 million people of all ages suffer from depression. The aim of our study was to determine the association between major dietary patterns and depression among type 2 diabetes patients. Methods: This cross-sectional study was conducted among 480 type 2 diabetes patients attending primary healthcare centers in Gaza Strip, Palestine. The depression, anxiety, stress scales (DASS, 21-items) questionnaire was used to measure the score of depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
(54 reference statements)
0
1
1
Order By: Relevance
“…This result was lower than that reported in some other research projects conducted in China (19%), Belgium (15.5%), Japan (38%), Pakistan (21.3%) and India (23%) (9-13). On the other hand, some research performed in Palestine on severely malnourished diabetic individuals suggests lower prevalence of 9.4% in comparison with our study (14). In a very recent study, malnutrition assessment showed that the prevalence of malnutrition in CKD patients (stage 4 and 5) with diabetes was higher than that in the uncombined group (9).…”
Section: Nutritional Assessment and Laboratory Findings In Dn Patientscontrasting
confidence: 82%
“…This result was lower than that reported in some other research projects conducted in China (19%), Belgium (15.5%), Japan (38%), Pakistan (21.3%) and India (23%) (9-13). On the other hand, some research performed in Palestine on severely malnourished diabetic individuals suggests lower prevalence of 9.4% in comparison with our study (14). In a very recent study, malnutrition assessment showed that the prevalence of malnutrition in CKD patients (stage 4 and 5) with diabetes was higher than that in the uncombined group (9).…”
Section: Nutritional Assessment and Laboratory Findings In Dn Patientscontrasting
confidence: 82%
“…However, dietary intakes of Middle-Eastern population have their own characteristics: Large intake of carbohydrates mostly in the form of refined grains, high intakes of trans and saturated fat, and low consumption of fruits and vegetables along with lack of alcohol intake makes their dietary pattern of great interest for the assessment of diet-disease relations [26]. Moreover, different from Western people, stressful life is highly prevalent in this region, which might further complicate diet-disease relations in this area [27]. Therefore, understanding the association between HEI-2010 with MetS and its component may be helpful in reducing disease-related premature mortality and improve outcomes among T2DM patients.…”
Section: Introductionmentioning
confidence: 99%